Effect of utilization of crude glycerol as substrate on fatty acid composition of an oleaginous yeast Rhodotorula mucilagenosa IIPL32: Assessment of nutritional indices. (August 2020) - Bansal, Neha; Dasgupta, Diptarka; Hazra, Saugata; Bhaskar, Thallada; Ray, Anjan; Ghosh, Debashish
Graphical abstract: Highlights: Yeast lipid has been evaluated for its potential for edible purpose. Crude glycerol upgraded and utilized for yeast lipid cultivation. Nutritional indices were evaluated for yeast oil. In-vitro toxicity studies confirmed the non-toxic nature of the yeast oil. Abstract: This work studied the use of crude glycerol obtained from biodiesel industry as substrate to generate yeast lipid from Rhodotorula mucilagenosa IIPL32 MTCC 25056. Crude glycerol is a low value by product obtained from biodiesel industry. Rhodotorula mucilagenosa IIPL32 MTCC 25056 was evaluated for its potential to produce lipid using crude glycerol as sole source of carbon. Under nitrogen limiting condition a lipid and biomass content of 5.6 g/L and19.7 g/L were obtained from crude glycerol. The fatty acid profile was found to be interestingly rich in oleic acid (61.88%), linoleic acid (16.17%) and linolenic acid (1.03%) comprising 80% of MUFA and PUFA of total lipid. Further, evaluations were attempted to compare MUFA rich yeast lipid against different plant-borne edible oils commonly used in India. In this study, nutritional indices were calculated to check feasibility of using yeast oil as a plausible blend to edible oil.